ANALYSIS OF MORAL VALUES IN THE NOVEL 'PUDARNYA PESONA CLEOPATRA' BY HABIBURRAHMAN EL-SHIRAZY AND ITS APPLICATION AS TEACHING MATERIAL FOR ANALYZING THE CONTENT AND LANGUAGE OF THE NOVEL FOR 12TH-GRADE HIGH SCHOOL STUDENTS - Wahyuni, Siti Sri; Subaweh, Ahmad Maskur; Naufal, Muji Zain (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
The advancement of globalization in today's society has had a negative impact on the manners and ethics of students. As a result, education plays a crucial role in shaping the character of students, particularly in terms of moral values. This study aims to examine the moral values depicted in the novel "Pudarnya Pesona Cleopatra" by Habiburrahman El-Shirazy and explore its potential as a learning resource in novel-based education. The research adopts a qualitative approach, focusing on the moral values portrayed in the novel. Data collection involves reading and writing methods. The findings reveal that the novel "Pudarnya Pesona Cleopatra" encompasses three main moral values: 1) individual morals, which pertain to one's relationship with oneself, 2) social morals, which involve interactions with others, and 3) religious morals, which encompass one's relationship with God. These three categories are further divided into 19 specific moral values, including honesty, never give up, sincerity, responsibility, firm stance, hard work, mutual love, parental concern for their children, parental obligations, children's affection for parents, helping, respecting each other, willing to sacrifice, respecting each other, advising, not imposing the will of others, always grateful, surrendering and praying, resulting in a total of 41 moral values. The outcomes of this study can be utilized as a valuable resource for teaching Indonesian language in the twelfth grade of high school, specifically in the context of Basic Competence (KD) 3.9, which focuses on analyzing the content and language of novels.